Porous polymer material as well as preparation method and application thereof
By introducing locally ordered structures and rigid nanoparticles into polymer microspheres and preparing anionic polymer materials, the shortcomings of polymer microspheres in terms of mechanical strength, thermal stability and adsorption capacity are solved, and efficient dye adsorption and contaminated water treatment are achieved.
Patent Information
- Application Number
- CN202510056003.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
AI Technical Summary
Polymer microspheres have shortcomings in mechanical strength, thermal stability and adsorption capacity, and are difficult to effectively apply in high external force environments and high temperature conditions, and their adsorption sites and adsorption efficiency need to be improved.
Using a porous polymer material with a locally ordered arrangement structure, chemically crosslinking unsaturated olefin monomers with rigid nanoparticles to form a material with high strength and adsorption amount, and anionic polymer material is prepared by alkali hydrolysis to improve adsorption efficiency.
It significantly improves the mechanical strength and adsorption ability of the material, enhances the selective adsorption of dyes, and is suitable for contaminated water treatment in high temperature and high external force environments.
Smart Images

Figure CN119859218A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous polymer material, and more particularly to a porous polymer material with a regular internal structure and a preparation method and application thereof. Background Art
[0002] Polymer microspheres refer to micron-sized spherical particles made of polymer materials. They have extremely high specific surface area, excellent dispersibility, and flexibly controllable physical and chemical properties. In practical applications, there are many types of commonly used polymer materials, such as polyacrylamide, polyacrylic acid, polystyrene, polyacrylate, polyvinyl alcohol, etc. Microspheres made of these polymer materials are widely used. In the field of biomedicine, they can be used as drug carriers and diagnostic reagents; in the field of coatings and inks, they can optimize performance; in the field of electronic materials, they can be used to prepare packaging materials.
[0003] Not only that, polymer microspheres have also shown significant potential in removing dyes. In industrial processes such as printing and dyeing, a large amount of these dye wastewaters are produced, causing serious pollution to the environment. Due to their special structure and properties, polymer microspheres can effectively adsorb and remove dye molecules from wastewater. For example, some polymer microspheres with porous structures have abundant pores that can provide a large number of adsorption sites, thereby smoothly adsorbing dye molecules. At the same time, by modifying the surface of polymer microspheres and introducing specific functional groups, their selective adsorption capacity for specific types of dyes can be enhanced. For example, polymer microspheres with cationic groups can efficiently adsorb negatively charged dye molecules. For example, the literature Cellulose nanocrystal-alginate hydrogel beads as novel adsorbents for organic dyes in aqueous solutions [J]. Cellulose, 2015, 22(6): 3725-3738. For the first time, CNCs-modified alginate microspheres were used as adsorbents to remove the natural dye methylene blue, and it was found that the higher the CNCs content, the higher the adsorption rate and the better the adsorption effect; for example, the literature Amine-functionalized cellulose nanofiber-sodium alginate-Fe(III)porous hollow beads for the efficient removal of Cr(VI) [J]. Cellulose, 2023, 30(6): 3807-3822. Using ferric chloride and glutaraldehyde as composite cross-linking agents, environmentally friendly cellulose nanofibers (CNFs), sodium alginate (SA) and amino-rich polyethyleneimine as raw materials were used to prepare porous hollow beads (CS-Fe@PEI), which had an excellent adsorption capacity of 32.298 mg / g for Cr(VI) at 526K.
[0004] However, polymer microspheres have some disadvantages and problems. For example, insufficient mechanical strength may lead to easy breakage or deformation in some applications that need to withstand large external forces, affecting their performance and service life; poor thermal stability will limit the application of polymer microspheres in high temperature environments; at the same time, as an adsorbent, its adsorption sites and adsorption capacity also need to be improved. Summary of the invention
[0005] As described in the background art, the polymer microspheres in the prior art have problems of poor strength, adsorption capacity and adsorption efficiency due to their microsphere structure. The present invention is made in view of the above situation.
[0006] One aspect of the present invention is to provide a porous polymer material having a porous pore structure, wherein at least part of the pores are in a locally ordered arrangement structure, so as to meet the above needs.
[0007] Another aspect of the present invention is to provide a porous polymer material incorporating rigid nanoparticles, which has high strength and adsorption capacity and can effectively adsorb dyes in wastewater.
[0008] Another aspect of the present invention is to provide use of the above polymer material for removing dyes from polluted water.
[0009] Another aspect of the present invention is to provide a method for removing dyes from polluted water, by contacting the polluted water with the porous polymer material or the modified anionic polymer material, a high dye adsorption efficiency can be obtained.
[0010] According to the purpose of this application, the present invention relates to a porous polymer material, the components of which are chemical cross-linking products of at least one unsaturated olefin monomer and at least one rigid nanoparticle; the porous polymer material has a pore structure inside, wherein at least one of the rigid nanoparticles has a non-spherically symmetric shape in the solution, and the pores at least partially form a basically ordered arrangement structure.
[0011] As a further improvement of the present application, the unsaturated ethylenic monomer is selected from the following group: acrylamide, acrylic acid, styrene, N-isopropylacrylamide, N,N-dimethylacrylamide, methacrylic acid and a mixture thereof.
[0012] As a further improvement of the present application, the non-spherically symmetric rigid nanoparticles are in the shape of rods, ribbons, sheets, needles or disks.
[0013] As a further improvement of the present application, the rigid nanoparticles are biological macromolecules.
[0014] As a further improvement of the present application, the biomacromolecule is selected from at least one of polypeptides, proteins, nucleic acids, polysaccharides and lipids.
[0015] As a further improvement of the present application, the biomacromolecule is selected from at least one of cellulose nanocrystals, cellulose nanofibers and hydroxypropyl cellulose.
[0016] As a further improvement of the present application, the polymer material is in a bulk form or a particulate form.
[0017] As a further improvement of the present application, when the polymer material is in the form of microparticles, the particle size of the polymer microparticles ranges from 10 to 1000 microns.
[0018] As a further improvement of the present application, the diameter of the pores is 1-70 microns.
[0019] On the other hand, the present application also discloses a method for preparing the above-mentioned porous polymer material, comprising the following steps:
[0020] Step (s1), dispersing rigid nanoparticles, unsaturated olefin monomers, a crosslinking agent and an initiator in water to form a dispersed phase solution;
[0021] Optional step (s2), dispersing the dispersed phase solution in a continuous phase containing an emulsifier to form emulsion droplets containing rigid nanoparticles;
[0022] Step (s3), polymerizing the unsaturated olefin monomers and / or the biomacromolecules to obtain the polymer material; wherein the polymerization includes self-polymerization of the unsaturated olefin monomers and / or cross-linking with a cross-linking agent and / or co-cross-linking with rigid nanoparticles;
[0023] In the case where step (s2) is not included, the obtained polymer material is in the form of a bulk; in the case where step (s2) is included, the obtained polymer material is in the form of microparticles.
[0024] As a further improvement of the present application, the polymerization method includes any one of ultraviolet curing or thermal curing.
[0025] As a further improvement of the present application, the emulsifier includes one or more of SPAN surfactants, Tween emulsifiers, cetyl polyethylene glycol and polyglycerol ricinoleate.
[0026] As a further improvement of the present application, the method further comprises a step of treating the polymer material with an alkali hydrolysis method to produce an anionic polymer material.
[0027] As a further improvement of the present application, the alkaline hydrolysis method comprises contacting the swollen polymer material with an alkaline solution at 50-60° C. for 5-8 hours.
[0028] As a further improvement of the present application, the alkaline solution is selected from an aqueous solution of an alkali metal hydroxide.
[0029] On the other hand, the present application also discloses an anionic polymer material prepared by the above preparation method. The present application also discloses the use of the above polymer material or anionic polymer material to remove dyes from polluted water.
[0030] On the other hand, the present application also discloses a method for removing dyes from contaminated water, comprising: contacting the contaminated water with a porous polymer material or an anionic polymer material for 60-120 minutes, so that at least 50% to at least 95% of one or more dyes are removed from the contaminated water.
[0031] As a further improvement of the present application, the dye is one or more of methylene blue, methyl orange, crystal violet, rhodamine B and malachite green.
[0032] Beneficial effects:
[0033] Compared with traditional pure polymer-based adsorbents, the present application adds rigid nanoparticles to the polymer system to enhance the mechanical strength of the polymer material. At the same time, the formed microparticles or overall material at least partially have an ordered internal structure and an arrangement structure of pore distribution, realizing an ordered pore structure and controllability in the polymer system, and making the force on the material surface more uniform. During the adsorption process, shrinkage / swelling is reduced and strength is provided to the polymer structure, further enhancing the mechanical properties and chemical stability of the microparticles, while increasing the adsorption sites of the material, making it have a high adsorption capacity for dyes, and suitable for further promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 (ab) are scanning electron microscope images of the CNC40-PAM60 of Example 1 and the overall polymer material of Example 4, respectively;
[0035] Figure 2 (ac) are cross-polarized light microscope images of polymer microparticles prepared in Examples 1-3, respectively;
[0036] Figure 3 is a particle size distribution diagram of the anionic polymer microparticles of Examples 1-3 and Comparative Examples 1-2;
[0037] Figure 4 is the adsorption of methylene blue by CNC40-PAM60, as shown by the Langmuir model ( Figure 4 a) Freundlich model ( Figure 4 b) DR model Figure 4 c) and Temkin model ( Figure 4 d) Adsorption isotherm diagram of the analysis;
[0038] Figure 5 The effects of CNC40-PAM60 of Example 1 and Integra-CNC40-APAM60 of Example 4 on the adsorption performance of cationic dyes methylene blue, crystal violet and rhodamine B wastewater;
[0039] Figure 6 CNC40-PAM60( Figure 6 a) and CNC0-PAM100( Figure 6 b) Microscope image after adsorption reaction. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in combination with the specific embodiments and drawings of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments, and are not intended to limit the scope of the present invention. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0041] As used herein, the terms "a", "an", "the" and similar terms used in the context of the present invention (especially in the claims) shall be construed to cover both the singular and the plural, unless otherwise indicated herein or the context clearly indicates the contrary.
[0042] Also as used herein, "and / or" refers to and encompasses any and all possible combinations of one or more of the associated listed items, as well as the lack of a combination when interpreted in the alternative ("or").
[0043] definition
[0044] The term "rigid nanoparticles" refers to biological macromolecules that present a non-spherically symmetric, rigid morphology when alone or dispersed in water. They may be disordered in the solvent, or form an ordered molecular arrangement of some lyotropic liquid crystals including nematic phase, smectic phase, cholesteric phase, columnar phase liquid crystal, etc. as the concentration of rigid nanoparticles increases.
[0045] The term "adsorption capacity" refers to the working capacity of the polymer material corresponding to the maximum amount of chemical species, such as dye, that can be adsorbed under specific operating conditions (such as temperature and pressure). When given in mg / g, the unit of adsorption capacity is equivalent to the number of grams of dye adsorbed per gram of polymer material.
[0046] In general, the present specification relates to porous polymer materials for dye adsorption and methods for synthesizing the same. The porous polymer materials may have properties that enhance adsorption and mechanical properties. Various optional details, aspects, and embodiments are further described herein.
[0047] In a first aspect, the present application relates to a porous polymer material, wherein the components of the polymer material are chemical cross-linking products of at least one unsaturated olefin monomer and at least one rigid nanoparticle; the porous polymer material has a pore structure inside, wherein at least one of the rigid nanoparticles has a non-spherically symmetric shape in a solution, and the pores at least partially form a basically ordered arrangement structure.
[0048] In the present application, when the rigid nanoparticles are dispersed in a solvent, an ordered molecular arrangement of a certain lyotropic liquid crystal including a nematic phase, a smectic phase, a cholesteric phase, a columnar phase liquid crystal, etc. is formed as the concentration increases. Liquid crystal materials with an ordered arrangement usually exhibit the birefringence property of light, so that the droplets or solvents containing non-spherically symmetric biomacromolecules formed in an ordered arrangement are clearly visible under a polarizing microscope and present a common liquid crystal conformation. Further, the non-spherically symmetric rigid nanoparticles are in the shape of rods, ribbons, sheets, needles or disks. In certain specific embodiments, the rigid nanoparticles can be selected from biomacromolecules, and further, the biomacromolecules are selected from at least one of polypeptides, proteins, nucleic acids, polysaccharides and lipids.
[0049] In a specific embodiment of the present application, the biomacromolecule is selected from cellulose nanocrystals. Cellulose nanocrystals (CNC) with a suitable aspect ratio and size distribution are a kind of biomacromolecules that have a certain rigidity in their solvent water and can form a lyotropic liquid crystal phase. Cellulose nanocrystals are a kind of rod-shaped nanoparticles obtained by removing the amorphous region from cellulose and retaining the crystalline region. The cellulose nanocrystals obtained by different methods have different functional groups on their surfaces. For example, the cellulose nanocrystals obtained by sulfuric acid hydrolysis have a large number of hydroxyl groups and sulfate groups on their surfaces; the cellulose nanocrystals obtained by TEMPO oxidation have a large number of hydroxyl groups and carboxyl groups on their surfaces. Therefore, cellulose nanocrystals have the characteristics of high crystallinity, high mechanical properties, large specific surface area, and high possibility of surface functionalization, and can form a lyotropic chiral nematic liquid crystal phase (between liquid and crystalline) at a specific concentration.
[0050] Specifically, according to the spirit of the present invention, by using rigid nanoparticles without spherical symmetry, porous polymer materials with orderly molecular arrangement, correspondingly controllable pores and excellent mechanical properties can be prepared, and the polymer materials are in the form of a whole or particles.
[0051] In certain embodiments, the unsaturated ethylenic monomer is selected from the group consisting of acrylamide (AM), acrylic acid (AA), styrene (SM), N-isopropylacrylamide (NIPAM), N,N-dimethylacrylamide (DMAA), methacrylic acid (MMA), and mixtures thereof. Particularly preferred monomers include acrylamide (AM) and acrylic acid (AA).
[0052] In certain embodiments, when the polymer material is in the form of microparticles, the microparticles have a particle size range of 10-1000 microns. Further, the microparticles have a particle size range of 50-60 microns.
[0053] In certain embodiments, the pore diameter is 1-70 microns.
[0054] In a second aspect, the present application relates to a method for preparing a porous polymer material, specifically comprising the following steps:
[0055] First, rigid nanoparticles, unsaturated olefin monomers, crosslinking agents and initiators are dispersed in water to form a dispersed phase solution; by controlling the specific rigid nanoparticles, including their aspect ratio, size distribution, etc. and their concentration in the aqueous phase, the rigid nanoparticles can be controlled to form an ordered or disordered state in the solvent. As a preferred embodiment, the mass ratio of the rigid nanoparticles to the unsaturated olefin monomer is 0.1-1. As a preferred embodiment, the mass ratio of the rigid nanoparticles to the unsaturated olefin monomer is 0.1-1.
[0056] Crosslinking agents play a vital role in the preparation of polymer materials. Its presence promotes the formation of a crosslinked network between polymer chains, and can enhance the structural stability of the polymer, so that it maintains its shape and integrity under different environmental conditions, and is not prone to rupture or deformation. Secondly, it helps to regulate the porosity and pore size of the material. By controlling the amount and type of the crosslinking agent, the pore structure inside it is accurately adjusted to meet specific application requirements, such as selective capture of different molecular sizes in the fields of adsorption and separation. Therefore, crosslinking agents are indispensable in the preparation of polymer materials, and have a significant optimization and guarantee effect on the performance and application of adsorbent materials. In a specific embodiment of the present application, the crosslinking agent is N, N'-methylenebisacrylamide. Initiator is a substance that can initiate monomers to undergo polymerization reactions. Factors such as the type, concentration and decomposition rate of the initiator will affect the generation rate of the polymer chain, thereby controlling the rate of the entire polymerization reaction. According to different initiation conditions, it is divided into photoinitiator, thermal initiator, and redox initiator. Among them, because the UV curing method has the advantages of fast, environmentally friendly and easy operation, in a specific embodiment of the present application, the photoinitiator is Irgacure 2959.
[0057] Secondly, an optional step is to disperse the dispersed phase solution in a continuous phase containing an emulsifier to form emulsion droplets containing rigid nanoparticles; the emulsifier can help form a uniform emulsion droplet dispersion and assist in the orderly arrangement of biomacromolecules in the emulsion droplets, and can prepare emulsion droplets with different orientation effects by controlling the temperature and orientation time, and then prepare microparticles or overall materials with corresponding orientation effects. By controlling the concentration, the basically ordered arrangement structure formed by the rigid nanoparticles in the emulsion droplets may include one or more regions; the above-mentioned basically ordered arrangement structure may be overall ordered or partially ordered. Within the scope of overall order, these basically ordered arrangement structures may form some special conformations in structure, such as ray-type, bipolar type or ring-type, for example, Figure 1As shown in the scanning electron micrograph of (a) (photographed after freeze-drying of the microparticles), the internal structure and pores of the anionic polymer microparticles tend to be arranged in an orderly manner along the radial direction, thus having a ray-type conformation.
[0058] In the above method, the emulsifier can be a SPAN surfactant, such as sorbitan monopalmitate (SPAN40), sorbitan monostearate (SPAN 60), sorbitan tristearate (SPAN 65), sorbitan monooleate (SPAN 80), sorbitan trioleate (SPAN 85), etc.; it can also be a Tween emulsifier, such as Tween 20, Tween 40, Tween 60, Tween 80 or Tween 85; or it can be cetyl polyethylene glycol, polyglycerol ricinoleate (PGPR), etc.
[0059] Finally, the unsaturated olefin monomers and / or biomacromolecules are polymerized together to obtain the polymer material; wherein the polymerization includes self-polymerization of the unsaturated olefin monomers and / or cross-linking with a cross-linking agent and / or co-cross-linking with rigid nanoparticles. wherein the polymerization can be performed by photochemistry, such as ultraviolet light curing, or by thermal polymerization.
[0060] When the optional steps are not included, the obtained polymer material is in a whole form, that is, a whole-form polymer material, which can be written as a whole polymer material; when the optional steps are included, the obtained polymer material is in the form of particles, that is, a particle-form polymer material, which can be written as polymer particles.
[0061] In certain embodiments, the above method further comprises a step of treating the polymer material with an alkali hydrolysis method to produce an anionic polymer material. The above alkali hydrolysis method comprises the following specific steps: contacting the swollen polymer material with an alkaline solution at 50-60° C. for 5-8 hours, and washing until neutral, and the anionic polymer material can be written as anionic polymer particles or anionic polymer material as a whole. In a specific embodiment, the alkaline solution is selected from an aqueous solution of an alkali metal hydroxide.
[0062] The concentration of sodium hydroxide is calculated based on the mass of the unsaturated olefin monomer. Taking acrylamide as an example, the concentration of sodium hydroxide is calculated using Formula I:
[0063]
[0064] Where W is the mass of sodium hydroxide, M is the mass of unsaturated olefin monomer, and h is the degree of hydrolysis.
[0065] In a fourth aspect, the present application relates to the use of the above polymer material or anionic polymer material to remove dyes from polluted water.
[0066] In a fifth aspect, the present application relates to a method for removing dyes from contaminated water, comprising: contacting the contaminated water with a porous polymer material or an anionic polymer material for 60-120 minutes, so that at least 50% to at least 95% of one or more dyes are removed from the contaminated water. In some embodiments, the type of dye is one or more of methylene blue, methyl orange, crystal violet, rhodamine B and malachite green. Specifically in the embodiment, the amount of the porous polymer material or the anionic polymer material is 0.3-0.8g / L, and in a more specific embodiment, the amount of the porous polymer material or the anionic polymer material is 0.4g / L.
[0067] The structure, preparation, separation effect and adsorption effect of the polymer material of the present invention will be described in detail below in conjunction with specific examples. In the embodiments of the present invention, unless otherwise specified, the ratios described are all mass ratios.
[0068] experiment
[0069] The following examples are provided for illustrative purposes only and are not intended to limit the invention as defined in the appended claims.
[0070] Embodiment 1:
[0071] 6 g of cellulose nanocrystals were weighed and dissolved in 100 ml of water, stirred evenly, and 9 g of acrylamide, 0.298 g of N,N'-methylenebisacrylamide (bis), and 0.298 g of photoinitiator (Irgacure 2959) were added to form a dispersed phase solution; the dispersed phase solution was added to 500 ml of liquid paraffin containing Span 80 (mass percentage concentration: 10%) at a stirring speed of 400 rpm, stirred and emulsified for 4 minutes, and after the reaction was completed, poured into a glass container, covered with a transparent glass cover, cured under 365 nm ultraviolet light for 1 hour, filtered, washed, and dried to obtain polymer microparticles. Under an orthogonal polarizing microscope, as shown in FIG. Figure 2 As shown in (a), these polymer particles can be observed to have obvious fingerprint textures, indicating that they have a ray-type internal structure and pore distribution.
[0072] The above polymer particles were functionalized by alkaline hydrolysis: 1.0129 g NaOH was weighed and dissolved in 594 ml aqueous solution, 10 g polymer particles were added, mixed evenly and placed in a water bath shaker, reacted at 60°C for 5 h, and anionic polymer particles were obtained, which were hereinafter referred to as "CNC40-APAM60". Figure 1 As shown in (a), the microstructure of the anionic polymer microparticles was characterized and analyzed by scanning electron microscopy (SEM), and it was found that they exhibited an obvious porous structure.
[0073] Example 2
[0074] 9 g of cellulose nanocrystals were weighed and dissolved in 100 ml of water, stirred evenly, and 9 g of acrylamide, 0.298 g of N,N'-methylenebisacrylamide (bis), and 0.298 g of a photoinitiator (Irgacure 2959) were added to form a dispersed phase solution; the dispersed phase solution was added to 500 ml of liquid paraffin containing Span 80 (mass percentage concentration: 10%) at a stirring speed of 400 rpm, stirred and emulsified for 4 minutes, and after the reaction was completed, poured into a glass container, covered with a transparent glass cover, cured under 365 nm ultraviolet light for 1 hour, filtered, washed, and dried to obtain polymer microparticles. Under an orthogonal polarizing microscope, as shown in FIG. Figure 2 As shown in (b), these polymer particles can be observed to have obvious fingerprint textures, indicating that they have a ray-type internal structure and pore distribution.
[0075] The above polymer particles were functionalized by alkaline hydrolysis: 1.0129 g NaOH was weighed and dissolved in 594 ml aqueous solution, 10 g polymer particles were added, mixed evenly and placed in a water bath shaker, reacted at 60° C. for 5 h to obtain anionic polymer particles, hereinafter referred to as “CNC50-APAM50”.
[0076] Example 3
[0077] 15 ml of acrylic acid was measured, and 30 ml of 6 mol / L NaOH solution was added, and the mixture was stirred evenly. Then, 6 g of cellulose nanocrystals, 0.4455 g of N,N'-methylenebisacrylamide (bis), and 0.4455 g of photoinitiator (Irgacure 2959) were added to form a dispersed phase solution. The dispersed phase solution was added to 500 ml of liquid paraffin containing Span 80 (mass percentage concentration: 10%) at a stirring speed of 400 rpm, and the mixture was stirred and emulsified for 4 min, and the rotation speed was maintained at 50 rpm, and the mixture was reacted for 30 min. After the reaction was completed, the mixture was poured into a glass container, covered with a transparent glass cover, and cured under 365 nm ultraviolet light for 1 h. The polymer particles were filtered, washed, and dried to obtain polymer microparticles, which are hereinafter referred to as "CNC-PAA". Under an orthogonal polarizing microscope, the polymer microparticles were observed to be CNC-PAA. Figure 2 As shown in (c), these polymer particles can be observed to have obvious fingerprint textures, indicating that they have a ray-type internal structure and pore distribution.
[0078] Example 4
[0079] Weigh 6g of cellulose nanocrystals and dissolve them in 100ml of water, stir evenly, add 9g of acrylamide, 0.298g of N,N'-methylenebisacrylamide (bis) and 0.298g of photoinitiator (Irgacure 2959) to form a dispersed phase solution; continue to stir the above dispersed phase solution until all substances are completely dissolved and mixed evenly to obtain a prepolymer solution. Take an appropriate amount of prepolymer solution and put it into a culture dish, cover it with a transparent glass cover, and cure it under 365nm ultraviolet light for 30min, then take out the obtained gel block from the mold and soak it in deionized water for a period of time to remove unreacted monomers and impurities. After soaking, take out the gel block, use filter paper to absorb the moisture on the surface, and obtain a pure gel block, that is, the overall polymer material.
[0080] like Figure 1 As shown in (b), the microstructure of the above-mentioned overall polymer material was characterized and analyzed by scanning electron microscopy (SEM), and it was found that it exhibited an obvious porous structure.
[0081] The above-mentioned integral polymer material was functionalized by alkaline hydrolysis method: 1.0129g NaOH was weighed and dissolved in 594ml aqueous solution, 10g of the above-mentioned integral polymer material was added, and after mixing evenly, it was placed in a water bath shaker and reacted at 60°C for 5h to obtain an integral anionic polymer material, hereinafter referred to as "Integra-CNC40-APAM60".
[0082] Comparative Example 1
[0083] 9 g of acrylamide was weighed and dissolved in 100 ml of water, stirred evenly, and 0.298 g of N, N'-methylenebisacrylamide (bis) and 0.298 g of photoinitiator (Irgacure 2959) were added to prepare a dispersed phase solution. The dispersed phase solution was added to 500 ml of liquid paraffin containing Span 80 (mass percentage concentration: 10%) at a stirring speed of 400 rpm, stirred and emulsified for 4 min, and after the reaction was completed, poured into a glass container, covered with a transparent glass cover, and cured under 365 nm ultraviolet light for 1 h, filtered, washed, and dried to obtain porous polymer particles. Under an orthogonal polarizing microscope, no obvious fingerprint texture was observed in these polymer particles, indicating that no cholesteric phase structure was formed inside the particles.
[0084] The above polymer particles were functionalized by alkaline hydrolysis: 1.0129 g NaOH was weighed and dissolved in 594 ml aqueous solution, 10 g polymer particles were added, mixed evenly and placed in a water bath shaker, reacted at 60°C for 5 hours to obtain anionic polymer particles, recorded as CNCO-APAM100.
[0085] Comparative Example 2
[0086] 2.25 g of cellulose nanocrystals were weighed and dissolved in 100 ml of water, stirred evenly, 9 g of acrylamide, 0.298 g of N, N'-methylenebisacrylamide (bis), and 0.298 g of a photoinitiator (Irgacure 2959) were added to form a dispersed phase solution; the dispersed phase solution was added to 500 ml of liquid paraffin containing Span 80 (mass percentage concentration: 10%) at a stirring speed of 400 rpm, stirred and emulsified for 4 minutes, and after the reaction was completed, poured into a glass container, covered with a transparent glass cover, and cured under 365 nm ultraviolet light for 1 hour, filtered, washed, and dried to obtain polymer microparticles. Since the concentration of cellulose nanocrystals in the dispersed phase solution was low, a liquid crystal phase could not be formed. Under an orthogonal polarizing microscope, no obvious fingerprint texture was observed for these polymer microparticles.
[0087] The above polymer particles were functionalized by alkaline hydrolysis: 1.0129 g NaOH was weighed and dissolved in 594 ml aqueous solution, 10 g polymer particles were added, mixed evenly and placed in a water bath shaker, reacted at 60° C. for 5 h, to obtain anionic polymer particles, hereinafter referred to as “CNC20-APAM80”.
[0088] Test Example 1: Particle Size Distribution Analysis
[0089] The functionalized polymer particles of Examples 1-3 and Comparative Examples 1-2 were washed to neutrality and then sieved through a 200-280 mesh sieve to select particles with substantially uniform particle size. The results showed that the particle size distribution range of each sample was basically the same. Figure 3 shown.
[0090] Test Example 2: Adsorption efficiency
[0091] 0.01 g of the sieved functionalized polymer particles of Test Example 1 and Integra-CNC40-APAM60 of Example 4 were weighed and added to 25 ml of 100 mg / L methylene blue solution, shaken at room temperature for 120 min, and centrifuged to obtain the supernatant. The concentration of methylene blue was measured by absorbance at 664 nm using a UV-visible spectrophotometer to evaluate the adsorption efficiency of the particles, as shown in Table 1.
[0092] The adsorption efficiency (R) is calculated using Formula II:
[0093]
[0094] In the formula, C0 and C e are the concentrations of methylene blue solution before adsorption and at adsorption equilibrium, respectively.
[0095] Table 1 Adsorption experimental data of Examples 1-4 and Comparative Examples 1-2
[0096]
[0097] From the adsorption experimental results in Table 1, it can be seen that in the acrylamide system, CNC40-PAM60 has a higher adsorption efficiency at adsorption equilibrium, and the error does not exceed 1%. This shows that the porous polymer particles with ordered pores play a positive role in the dye adsorption process. Its ordered pore structure may provide more convenient diffusion channels and more adsorption sites for methylene blue molecules, thereby promoting the efficient adsorption process. Similarly, anionic polymer particles prepared using other polymer monomers, such as acrylic acid, also have a high adsorption efficiency, and the adsorption efficiency of the overall material in non-particle form can still reach more than 70%. This means that different types of polymer particles have unique value and potential in dye adsorption applications, providing a strong experimental basis and research direction for expanding a variety of adsorption material systems.
[0098] Test Example 3:
[0099] Adsorption isotherms are usually used to calculate the maximum adsorption capacity by studying the interaction between the adsorbent and the adsorbate. In order to further understand the adsorption behavior of the particles, the adsorption data of CNC40-PAM60 in Table 1 were fitted using the Langmuir isotherm model, the Freundlich isotherm model, the DR isotherm model and the Temkin isotherm model, respectively. The fitting equations are as follows.
[0100] Langmuir Model: C e / Q e =1 / Q m K L +C e / Q m
[0101] Freundlich model: lnQ e =lnK F +lnC e / n
[0102] DR Model: LnQ e =lnQ m -K D ε 2
[0103] Temkin Model: Q e =RTlnA / B+RTlnC e / B
[0104] Among them, C e is the mass concentration of methylene blue in the solution at adsorption equilibrium (mg / L); Q eis the equilibrium adsorption capacity (mg / g); Q m is the maximum adsorption capacity (mg / g); K L (L / mg) is the Langmuir constant; K F (mg˙g -1 ) is the Freundlich constant; n is the model index, K D is the DR model constant; ε is equal to RTln(1+1 / Ce); B is the Temkin model constant; A is related to the maximum binding energy of the adsorbent.
[0105] based on Figure 4 Based on the results, the maximum adsorption capacity, Langmuir constant, Freundlich constant and correlation coefficient were extracted from the adsorption isotherm of methylene blue dye on CNC40-PAM60 microparticles, and these parameters are listed in Table 2.
[0106] Table 2 Parameters extracted from the adsorption isotherms of methylene blue using the Langmuir model, Freundlich model, DR model and Temkin model
[0107]
[0108]
[0109] It can be seen from the data in Table 2 that the methylene blue adsorption isotherm data can be better described by the Langmuir model because it shows a better correlation coefficient (R2=0.9985) and a larger adsorption capacity (490.12 mg / g) than the DR model, and also indicates that the adsorption of methylene blue dye by the polymer microparticles of the present invention is a monolayer adsorption.
[0110] Test Case 4: Wastewater Treatment
[0111] Three dyes, methylene blue, crystal violet and rhodamine B, were selected to test the adsorption selectivity and adsorption mechanism of CNC40-PAM60 particles and Integra-CNC40-APAM60 of Example 4.
[0112] CNC40-PAM60 particles and Integra-CNC40-APAM60 were used to treat wastewater containing methylene blue, crystal violet and rhodamine B, respectively. The concentrations of wastewater containing methylene blue, crystal violet and rhodamine B were 100 mg / L, 100 mg / L and 50 mg / L, respectively. Samples were collected at appropriate time intervals and the concentrations were determined using a spectrophotometer. The time interval was set to 120 minutes, and then the equilibrium solution concentration was measured. The adsorption efficiency was calculated using Formula II.
[0113] The results are as follows Figure 5As shown, when the wastewater solution is 25 ml and the weight of the two anionic polymer materials is 0.01 g, the adsorption efficiency of CNC40-PAM60 for methylene blue is 93.8155%, and the adsorption efficiency for crystal violet is 96.2691%. Even for rhodamine B, which has a relatively complex structure and is difficult to adsorb, its adsorption efficiency can reach more than 50%. In comparison, the adsorption efficiency of the overall material for methylene blue is 70.338%, and the adsorption efficiency for crystal violet is 69.2117%. The adsorption efficiency for rhodamine B is significantly reduced, only 24.5296%.
[0114] Test Example 5: Volume Change after Adsorption
[0115] The volume changes of CNC0-APAM100 and CNC40-APAM60 after the adsorption reaction of Test Example 2 were tested. Figure 6 It can be seen that the volume of CNC0-APAM100 is significantly reduced after the adsorption reaction compared with CNC40-APAM60. Since the surface of the functionalized particles is rich in carboxyl groups, they usually have a large swelling rate in aqueous solution. However, the ordered arrangement of particles containing cellulose nanocrystals restricts the movement of polymer molecular chains, thereby reducing the swelling rate and reducing the volume change of particles after adsorption, further verifying that the rigid structure and high strength of cellulose nanocrystals can improve the mechanical strength of polymer particles and enhance their adsorption capacity.
[0116] Although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0117] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A porous polymer material, characterized in that The components of the polymer material are chemical crosslinking products of at least one unsaturated olefin monomer and at least one rigid nanoparticle; the porous polymer material has a pore structure inside, wherein at least one of the rigid nanoparticles has a non-spherically symmetric shape in the solution, and the pores at least partially form a basically ordered arrangement structure.
2. The polymer material according to claim 1, characterized in that The unsaturated ethylenic monomer is selected from the group consisting of acrylamide, acrylic acid, styrene, N-isopropylacrylamide, N,N-dimethylacrylamide, methacrylic acid and a mixture thereof.
3. The polymer material according to claim 1, characterized in that The non-spherically symmetric rigid nanoparticles are in the shape of rods, ribbons, sheets, needles or disks.
4. The polymer material according to claim 1, characterized in that Rigid nanoparticles are biomacromolecules.
5. The polymer material according to claim 4, characterized in that The biomacromolecule is selected from at least one of polypeptides, proteins, nucleic acids, polysaccharides and lipids; Preferably, the biomacromolecule is selected from at least one of cellulose nanocrystals, cellulose nanofibers and hydroxypropyl cellulose.
6. The polymer material according to claim 1, characterized in that The polymer material is in the form of a bulk or particulates.
7. The polymer material according to claim 6, characterized in that When the polymer material is in the form of microparticles, the particle size of the microparticles may be in the range of 10-1000 microns.
8. The polymer material according to claim 1, characterized in that The pore diameter is 1-70 microns.
9. The method for preparing a porous polymer material according to claims 1 to 8, characterized in that: The steps include: Step (s1), dispersing rigid nanoparticles, unsaturated olefin monomers, a crosslinking agent and an initiator in water to form a dispersed phase solution; Optional step (s2), dispersing the dispersed phase solution in a continuous phase containing an emulsifier to form emulsion droplets containing rigid nanoparticles; Step (s3), polymerizing the unsaturated olefin monomers and / or the biomacromolecules to obtain the polymer material; wherein the polymerization includes self-polymerization of the unsaturated olefin monomers and / or cross-linking with a cross-linking agent and / or co-cross-linking with rigid nanoparticles; In the case where step (s2) is not included, the obtained polymer material is in the form of a bulk; in the case where step (s2) is included, the obtained polymer material is in the form of microparticles.
10. The method according to claim 9, characterized in that The polymerization method includes any one of ultraviolet curing or thermal curing.
11. The method according to claim 9, characterized in that The emulsifier includes one or more of SPAN surfactants, Tween emulsifiers, cetyl polyethylene glycol and polyglycerol ricinoleate.
12. The method according to claim 9, characterized in that The method further comprises the step of treating the polymer material with alkaline hydrolysis to produce an anionic polymer material.
13. The method according to claim 12, characterized in that The alkaline hydrolysis method comprises contacting the swollen polymer material with an alkaline solution at 50-60° C. for 5-8 hours.
14. The method according to claim 13, characterized in that The alkaline solution is selected from aqueous solutions of alkali metal hydroxides.
15. An anionic polymer material produced by the method of any one of claims 12 to 14.
16. Use of the polymer material according to any one of claims 1 to 8 or the anionic polymer material according to claim 15 for removing dyes from polluted water.
17. A method for removing dye from contaminated water, comprising: Contacting the contaminated water with the porous polymer material of claims 1-8 or the anionic polymer material of claim 15 for a period of 60-120 minutes results in at least 50% to at least 95% of the one or more dyes being removed from the contaminated water.
18. The method of claim 17, wherein the dye is one or more of methylene blue, methyl orange, crystal violet, rhodamine B and malachite green.